Impact of Humor Advertising on Brand Purchase Strategy - Palikhe, Amin (Journal of Nepalese Business Studies, 2019)
The humor advertisement is important for every types of marketer. The main aim of the study is to analyze the impact of humor advertisement on the brand purchasing strategy of consumers. This study used descriptive research design by testing the hypothesis with dependent and independent variables. The questionnaire based survey has been undertaken upon the sample of 136 respondents. Furthermore, data analysis has been carried forward with the help of SPSS through regression and correlation. The results reveal that there is no significant relationship exists between the independent variable (humor advertisement) and the dependent variables (brand attitude, brand memories, purchase intention). There is low correlation between humor advertisement and brand attitude that shows p<0.1. Industries have been spending huge amount of money on humor advertisement but the study has also revealed that there is no significant changes in brand purchase strategy of consumer by appealing humor advertising. Test results of correlation and regression shows that humor advertisement can’t make brand purchase strategy. Therefore study of consumer behavior is important to create brand purchase strategy and spending nature of consumer towards advertised products.